On Orsunius V. Seven new species from Borneo and Vietnam (Coleoptera: Staphylinidae: Paederinae: Medonina) - Volker Assing (Contributions to Entomology)
Seven species of Orsunius Assing, 2011 are described and illustrated, six of them from Borneo and one from Vietnam: Orsunius weigeli spec. nov. (North Vietnam), O. floreni spec. nov. (Malaysia: Sabah), O. flavoniger spec. nov. (Malaysia: Sabah), O. incitatus spec. nov. (Malaysia: Sabah), O. curvicollis spec. nov. (Malaysia: Sabah), O. tricolor spec. nov. (Malaysia: Sabah), and O. arboris spec. nov. (Malaysia: Sabah). The genus now includes 31 named extant species distributed in the southern East Palaearctic, the Oriental, and the northern Australian regions.